2015
DOI: 10.4314/ahs.v15i2.26
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence in type 2 diabetes patients: study of patients in Alimosho General Hospital, Igando, Lagos, Nigeria.

Abstract: Background: Poor adherence is an obstacle in therapeutic control of diabetes. Despite the advances in the treatment of diabetes mellitus over the years, diabetes places an immense burden on the individuals living with the condition, their families and the overall health care system. Objective: Evaluation of the impact of medication adherence on the clinical outcomes of type 2 diabetes patients at Alimosho general hospital, Igando Lagos state. Method: The medication adherence study was both descriptive (retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
74
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(94 citation statements)
references
References 17 publications
18
74
1
1
Order By: Relevance
“…Lower than this adherence rate was reported from different areas of the world such as 43.34% in southern India [15] 68.8% in Assela general hospital, Ethiopia, [16] 45% in Sudan [17] 66.8% in Tikur Anbessa specialized hospital, Addis Ababa, Ethiopia, [18] and 40.95% in southern Ethiopia [19]. In the contrary, better than the present value was also reported from various areas including 72.5% in eastern Nigeria [11] 83.3% in eastern Uganda [20] 86.8 in Lagos, Nigeria [21] and 75.7% in Jimma University specialized hospital, southwest Ethiopia [22] This difference is partly ascribed to variation of socio-demographic and socioeconomic characteristics as well as other contributing factors that can somehow affect optimal adherence in the aforementioned studies. Non-adherence to medications among diabetic patients might result in poor glycemic control.…”
Section: Disscussion Adherence To Medicationmentioning
confidence: 55%
“…Lower than this adherence rate was reported from different areas of the world such as 43.34% in southern India [15] 68.8% in Assela general hospital, Ethiopia, [16] 45% in Sudan [17] 66.8% in Tikur Anbessa specialized hospital, Addis Ababa, Ethiopia, [18] and 40.95% in southern Ethiopia [19]. In the contrary, better than the present value was also reported from various areas including 72.5% in eastern Nigeria [11] 83.3% in eastern Uganda [20] 86.8 in Lagos, Nigeria [21] and 75.7% in Jimma University specialized hospital, southwest Ethiopia [22] This difference is partly ascribed to variation of socio-demographic and socioeconomic characteristics as well as other contributing factors that can somehow affect optimal adherence in the aforementioned studies. Non-adherence to medications among diabetic patients might result in poor glycemic control.…”
Section: Disscussion Adherence To Medicationmentioning
confidence: 55%
“…Worldwide studies using various research assessment instruments and systematic reviews have addressed issues of poor medication adherence among diabetes patients. [17][18][19][20][21][22]37 In this study, medication adherence was assessed using MMAS-8. It is a reliable and validated scale.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients. 21,[28][29][30][31][32][33] AIM Therefore, this study was conducted to assess the medication adherence among type II diabetic patients attending a tertiary care hospital in Navi Mumbai, India.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide studies using various research assessment instruments and systematic reviews have addressed issues of poor medication adherence among diabetic patients. [17][18][19] It was observed that many patients forgot to take medicines with them when they are away from home. Others felt that it was very difficult to adhere to treatment plans and so stopped the medications.…”
Section: Discussionmentioning
confidence: 99%